Pengaruh Website “Edukasi Pajak” dalam Meningkatkan Literasi dan Kesadaran Pajak Siswa Sekolah Menengah Atas - Triatmi Puji Hastuti; Muhammad Sabandi; Budi Wahyono (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
Tax education for senior high school students is essential for developing future taxpayers who possess adequate tax literacy and awareness. This study aims to examine the effectiveness of the Tax Education website by analyzing the effects of information quality, system quality, and service quality on usage intention and user satisfaction, as well as their effects on students’ tax literacy and awareness. A quantitative approach was employed involving 280 senior high school students in Central Java selected through purposive sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed through partial least squares structural equation modeling using SmartPLS 4.0. The findings reveal that information quality, system quality, and service quality positively and significantly affect usage intention and user satisfaction. Usage intention also positively affects user satisfaction. Furthermore, usage intention and user satisfaction positively and significantly improve students’ tax literacy and awareness. Service quality has the strongest effect on usage intention, while user satisfaction has the strongest effect on tax awareness. These findings imply that improving content accuracy, system accessibility, technical stability, and interactive services can strengthen the effectiveness of digital tax education. Schools and tax authorities should therefore integrate the website into structured and sustainable tax-learning activities.